ANALISIS PENGEMBANGAN PERBANKAN SYARIAH BERDASARKAN AZAS KEKHUSUSAN ACEH DAN QANUN LEMBAGA KEUANGAN SYARIAH DI KABUPATEN PIDIE - Nelliyana Nelliyana; Eva Sulastri Sagita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The purpose of this study is to determine: (1) analysis of the development of Islamic banking in terms of service quality; (2) analysis of sharia banking development in terms of banking services; (3) analysis of the development of sharia banking from both sides, namely the quality of services and banking services together. The population in this study is the priority customers at Bank Syariah Indonesia in Pidie Regency totaling 100 people. The research aims to obtain information about the analysis at the time the research was conducted. The research instrument is a questionnaire/questionnaire with a Likert scale model. Requirements test was conducted to test normality, linearity and independence between independent variables. The data analysis technique used is the multiple regression techniques. The results showed: (1) there is a significant effect between service quality on the development of Islamic banking with t count = 2,567; (2) there is a significant influence between banking services on banking development with t count = 9.051; and (3) there is a positive and significant influence jointly between the quality of banking services and services on the development of Islamic banking with Fcount = 56.948. The suggestions submitted are; (1) Expected to the Bank Indonesian Sharia KCP. Pidie improves technology to match the rapid increase in technology in the banking sector, conducts more active socialization or public education; (2) Bank Syariah Indonesia further improves the quality of banking services, so as to increase the number of customers and retain existing customers at Bank Syariah Indonesia.Keywords : Analysis, Development, Banking